2016
DOI: 10.19056/ijmdsjssmes/2016/v5i2/100596
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathological Study of Acute Appendicitis in Eastern India

Abstract: Background: Appendicitis is the most commonly performed emergency abdominal surgery. An accurate and timely diagnosis of acute appendicitis remains a challenge. Objective: This study was performed to determine and correlate between the clinical patterns of acute appendicitis, laboratory and ultrasound findings and pathology found in appendicectomy specimens to help timely diagnosis and reduce negative appendicectomy rate. Methods: This is a cross sectional study, detailed history and clinical examination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
2
6
2
Order By: Relevance
“…In the present study, pain and tenderness were the most common symptoms present in all patients followed by nausea/vomiting in 61.5% and anorexia in 48.1%. These findings are in accordance with the literature [18][19][20].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, pain and tenderness were the most common symptoms present in all patients followed by nausea/vomiting in 61.5% and anorexia in 48.1%. These findings are in accordance with the literature [18][19][20].…”
Section: Discussionsupporting
confidence: 94%
“…10 In the present study, abdominal pain was seen in 84% of patients which was contrary to the study conducted by Ekka et al, which was seen in 100% of patients. 13 Anorexia was seen in 90% of patients in the present study, whereas anorexia was seen in 61% of patients in a study by Berry et al 14 87% of patients had nausea/vomiting in this present study, which was similar to a study by Kodliwadmath. 15 45% of patients had fever in this study, but Reddy et al reported fever in 76% of patients in their study.…”
Section: Discussionsupporting
confidence: 87%
“…16 94% of patients in this study had leukocytosis, but Ekka et al reported leukocytosis in 66.4% of patients in their study. 13 Tenderness in right inguinal fossa was seen in all 100% of patients and rebound tenderness was seen in 34 patients. An eastern Indian study reported tenderness in right inguinal fossa in 89.6% and rebound tenderness in 72.8% of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Ekka et al studied the clinical presentation of 125 patients for a period of 2 years. 6 Alvarado scoring in the evaluation of acute appendicitis was studied by Özsoy et al amongst 156 patients and by Mahesh et al amongst 50 patients. 7,8 The comparison of their findings with our present study is shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%